2012
DOI: 10.1139/g11-075
|View full text |Cite
|
Sign up to set email alerts
|

Identification of salt-tolerant QTLs with strong genetic background effect using two sets of reciprocal introgression lines in rice

Abstract: Effect of genetic background on detection of quantitative trait locus (QTL) governing salinity tolerance (ST) was studied using two sets of reciprocal introgression lines (ILs) derived from a cross between a moderately salinity tolerant japonica variety, Xiushui09 from China, and a drought tolerant but salinity susceptible indica breeding line, IR2061-520-6-9 from the Philippines. Salt toxicity symptoms (SST) on leaves, days to seedling survival (DSS), and sodium and potassium uptake by shoots were measured un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 43 publications
4
74
0
Order By: Relevance
“…Shan et al (2006) detected SSR markers linked to salt tolerance in wheat by using the bulked segregation analysis method combined with SSR markers and then located the salt tolerance-related genes. Cheng et al (2012) Although many EST-SSR markers have been developed from G. hirsutum, G. arboreum, G. raimondii, G. barbadense, and G. herbaceum, no EST-SSR primers have been developed specifically using salt-tolerance ESTs. In this research, 132 pairs of EST-SSR primers were developed based on cotton salt-tolerance ESTs obtained from BLAST with Arabidopsis salt-tolerance genes, so as to serve cotton salt-tolerance molecular breeding efforts.…”
Section: Development Amplification and Characteristics Of The Salt-mentioning
confidence: 99%
“…Shan et al (2006) detected SSR markers linked to salt tolerance in wheat by using the bulked segregation analysis method combined with SSR markers and then located the salt tolerance-related genes. Cheng et al (2012) Although many EST-SSR markers have been developed from G. hirsutum, G. arboreum, G. raimondii, G. barbadense, and G. herbaceum, no EST-SSR primers have been developed specifically using salt-tolerance ESTs. In this research, 132 pairs of EST-SSR primers were developed based on cotton salt-tolerance ESTs obtained from BLAST with Arabidopsis salt-tolerance genes, so as to serve cotton salt-tolerance molecular breeding efforts.…”
Section: Development Amplification and Characteristics Of The Salt-mentioning
confidence: 99%
“…Recent studies on molecular quantitative genetics of complex traits demonstrated the fact that even though the germplasms or modern varieties do not show stress tolerance, they do harbor some excellent genes such as drought tolerance Lafitte et al 2006;He et al 2010), salt tolerance (Cheng et al 2012;Wang et al 2012), and cold tolerance (Andaya and Tai 2006;Jiang et al 2008). Such favourable genes were found to be 'hidden' in germplasms, and advance backcross populations appears to be an effective way to mine them by introgressing and further pyramiding favourable genes of parents and different donors with molecular marker technologies Guan et al 2010).…”
Section: Implications For Rice Breeding Of Dtmentioning
confidence: 99%
“…A large number of quantitative trait loci (QTLs) for seed germination and seedling growth under normal (Cui et al 2002;Zhang et al 2005;Wang et al 2010;Li et al 2011;Cheng et al 2013Cheng et al , 2014, drought (Teng et al 2002;Zhou et al 2006;Kamoshita et al 2008;Hu et al 2011;Ding et al 2011) and salt (Pandit et al 2010;Ahmadi et al 2011;Tian et al 2011;Wang et al 2011b;Cheng et al 2012;Wang et al 2012a, b) conditions have been identified by the traditional biparental mapping approach in rice. However, the genetic relationship of seed germination and/or seedling growth between multiple conditions at the whole-genome level is still unclear.…”
Section: Introductionmentioning
confidence: 99%